Legality of Artificial Intelligence-Generated Advertising in Commercial Activities Based on Legal Certainty - Putri, Fallen Annisa Aji; Sakti, Muthia; Winanti, Atik (Journal of Law, Politic and Humanities, 2025)
To understand and analyze the legality concerning the use of artificial intelligence in commercial activities. To explore and analyze the legal certainty of advertising generated by artificial intelligence. This research also helps the author gain insight and firsthand knowledge on how AI-generated advertising is regulated under Indonesian law. Through this normative legal method, results will be obtained that align with practical applications. This will make the research more concrete and accountable for its authenticity and validity. Artificial intelligence technology is fundamentally developed by generating results through the input of big data or pre-existing data, which is then trained to produce the desired outcomes. Although the technology is created to ease human life, its development has led to complexities, particularly in relation to the law. One current debate centers on the copyright of works created by artificial intelligence (AI). This has become a polemic due to the illegal use of data for training purposes